SISTEM INFORMASI KEGIATAN BERBASIS WEB MOBILE PADA VIHARA LAHUTA MAITREYA DI MAKASSAR - Billy Tany Awan; Afifah; Ahyar Muawwal (STMIK KHARISMA Makassar, 2021)
Vihara Lahuta Maitreya still uses live announcements so it is difficult to provide information to the congregation. The testing method used in this study is the black box tester. The techniques that are carried out are login testing, registration testing, password forgetting testing, notification input testing aims to provide schedule acceleration information to users, activity testing provides information on what events to do in the future, learning input testing is useful for users who want to learn in PDF form, e-mail receipt. From the tests carried out, it can be said that the application runs as expected because it can help parties in delivering information that is directly sent to parties through the community, making it easier to convey information from parties through as admin delivered via e-mail. to people who have registered previously.